Evolutions in estuary governance? Reflections and lessons from Australia, France and New Caledonia. (February 2020) - Daniell, Katherine A.; Plant, Roel; Pilbeam, Victoria; Sabinot, Catherine; Paget, Nicolas; Astles, Karen; Steffens, Ruben; Barreteau, Olivier; Bouard, Severine; Coad, Peter; Gordon, Anna; Ferrand, Nils; et al.
Abstract: Estuaries are cradles of life for the communities who live around and within them. They are valued in multiple ways for the services they provide to humans, including food production, recreation, water purification, navigation and amenity. Various groups of stakeholders all place different importance on these values, how their needs and practices interact, and what it means to effectively manage an estuary towards a range of desirable goals. This typically creates value conflicts over how estuaries should be managed. Navigating such conflicts requires governance arrangements and methods that allow multiple parties to find a common path forward. Using Evolutionary Governance Theory (EGT) and a hybrid analytic framework incorporating aspects of multi-level/multi-scalar governance, risk governance and territorial intelligence theory, this paper explores the (co-)evolution of governance processes by analysing lessons learnt from action in and observation of estuaries in Australia (Lower Hawkesbury), France (Thau) and New Caledonia (Thio). A multi-method research approach to data collection was used and comparative analysis across the three estuaries undertaken to understand the evolutions in each of their governance systems. From this analysis, several reflections and lessons for the governance of other land-sea systems emerge on: the importance of boundary organisations and boundary negotiations in re-defining integrated approaches to land-sea governance; how particular information systems or models, as well as discourses from other key actors shape co-evolutions of estuarine governance; and that risks or shocks still appear to be the catalysers of new forms of collective action and major reconfigurations and evolutions of estuarine governance. Highlights: Risks/shocks are principal catalysers of new forms of collective action and major reconfigurations of estuarine governance. Boundary negotiations between actors and organisations are key in re-defining integrated approaches to land-sea governance. Brokering organisations, information systems, models and discourses are non-human actors that shape governance co-evolutions.